Photocatalytic Effects of Nanoparticles of TiO2 in Order to Design Self-Cleaning Textiles - Norouzi, Mohammad; Maleknia, Laleh (Asian Journal of Chemistry, 2010)
Titanium dioxide nanoparticle shows photo catalytic effect. It can decompose organic structures (pollution) with touch its surface also. It shows superhydrophilic effect. According to lotus leaf model, we provided textiles with withstanding penetration of liquids without using any resin. So, the textiles firstly withstand pollution and if they pollute, they can decompose the pollution structure under UV radiation. In this work, we studied the effect of nano silver and enhancement of electron-hole separation by the electron trapping and reduction of energy gap of titania. In addition to that, adding nano silica to titania, demonstrated higher photocatalytic and superhydrophilc activity in comparison to pure TiO2.